Can hepatic resection provide a long‐term cure for patients with intrahepatic cholangiocarcinoma?. Issue 22 (11th August 2015) - Spolverato, Gaya; Vitale, Alessandro; Cucchetti, Alessandro; Popescu, Irinel; Marques, Hugo P.; Aldrighetti, Luca; Gamblin, T. Clark; Maithel, Shishir K.; Sandroussi, Charbel; Bauer, Todd W.; Shen, Feng; Poultsides, George A.; et al.
Abstract : BACKGROUND: A patient can be considered statistically cured from a specific disease when their mortality rate returns to the same level as that of the general population. In the current study, the authors sought to assess the probability of being statistically cured from intrahepatic cholangiocarcinoma (ICC) by hepatic resection. METHODS: A total of 584 patients who underwent surgery with curative intent for ICC between 1990 and 2013 at 1 of 12 participating institutions were identified. A nonmixture cure model was adopted to compare mortality after hepatic resection with the mortality expected for the general population matched by sex and age. RESULTS: The median, 1‐year, 3‐year, and 5‐year disease‐free survival was 10 months, 44%, 18%, and 11%, respectively; the corresponding overall survival was 27 months, 75%, 37%, and 22%, respectively. The probability of being cured of ICC was 9.7% (95% confidence interval, 6.1%‐13.4%). The mortality of patients undergoing surgery for ICC was higher than that of the general population until year 10, at which time patients alive without tumor recurrence can be considered cured with 99% certainty. Multivariate analysis demonstrated that cure probabilities ranged from 25.8% (time to cure, 9.8 years) in patients with a single, well‐differentiated ICC measuring ≤5 cm that was without vascular/periductal invasion and lymph nodes metastases versus <0.1% (time to cure, 12.6 years) among patients with all 6 of these risk factors. A model with which to calculate cure fraction and time to cure was developed. CONCLUSIONS: The cure model indicated that statistical cure was possible in patients undergoing hepatic resection for ICC. The overall probability of cure was approximately 10% and varied based on several tumor‐specific factors. Cancer 2015;121:3998–4006. © 2015 American Cancer Society . Abstract : In the current study, the probability of a patient being statistically cured of intrahepatic cholangiocarcinoma by hepatic resection is analyzed. A nonmixture cure model was adopted to compare mortality after hepatic resection with the mortality expected for the general population matched by sex and age. The overall probability of cure appears to be approximately 10% and varies based on several tumor‐specific factors such as tumor number and size, histological grade, vascular/periductal invasion, and lymph node metastasis.